A high‐throughput screening method for determination of multi‐antibiotics in animal feed. Issue 18 (24th July 2019) - Qian, Mingrong; Zhang, Xiaoming; Zhao, Huiyu; Ji, Xiaofeng; Li, Xiaodan; Wang, Jianmei; Wu, Huizhen; Xu, Jie; Li, Zuguang
Abstract: A high‐throughput method based on ultrasonic‐assisted extraction, 96‐well plate thin‐film microextraction was established to determinate 18 antibiotics in animal feed. In this method, the extraction was implemented by ultrasonic‐assisted extraction for 30 min with disodium ethylenediaminetetraacetic acid‐McIlvaine buffer (pH 5) containing 6% sodium chloride w/v, purified by thin‐film microextraction and combined with 96‐well plate system to improve the efficiency. Optimization of thin‐film microextraction conditions was performed by methods of single factor and response surface, and finalized as: condition time: 20 min; adsorption time: 55 min; washing time: 5 s with water; desorption time: 30 min with acetonitrile/water (8:2, v/v) containing 0.1% formic acid v/v. Evaluation of different extractive phases showed that polystyrene‐divinylbenzene‐polyacrylonitrile was the optimum coating. The analysis was performed by ultra‐high performance liquid chromatography with tandem mass spectrometry. Recovery, inter‐ and intraday precision, linearity, limit of detection, and quantitation were evaluated. The average recoveries of 18 antibiotics were 66.6–93.5% at three spiked levels, intraday precision was 1–8.4%, and interday precision was 3.0–16.4%. The linearity was good for r 2  > 0.99. Limits of detection and quantification were found in the range of 1–14 and 4–48 µg/kg, respectively.